Catalyzing Interdisciplinary Research and Training: Initial Outcomes and Evolution of the Affinity Research Collaboratives Model. (October 2017) - Ravid, Katya; Seta, Francesca; Center, David; Waters, Gloria; Coleman, David
Abstract : Team science has been recognized as critical to solving increasingly complex biomedical problems and advancing discoveries in the prevention, diagnosis, and treatment of human disease. In 2009, the Evans Center for Interdisciplinary Biomedical Research (ECIBR) was established in the Department of Medicine at Boston University School of Medicine as a new organizational paradigm to promote interdisciplinary team science. The ECIBR is made up of affinity research collaboratives (ARCs), consisting of investigators from different departments and disciplines who come together to study biomedical problems that are relevant to human disease and not under interdisciplinary investigation at the university. Importantly, research areas are identified by investigators according to their shared interests. ARC proposals are evaluated by a peer review process, and collaboratives are funded annually for up to three years. Initial outcomes of the first 12 ARCs show the value of this model in fostering successful biomedical collaborations that lead to publications, extramural grants, research networking, and training. The most successful ARCs have been developed into more sustainable organizational entities, including centers, research cores, translational research projects, and training programs. To further expand team science at Boston University, the Interdisciplinary Biomedical Research Office was established in 2015 to more fully engage the entire university, not just the medical campus, in interdisciplinary research using the ARC mechanism. This approach to promoting team science may be useful to other academic organizations seeking to expand interdisciplinary research at their institutions.